Relational Capital – Theoretical Fundamentals and Application in Retailing - Nikolova, Ivanka (Research Papers, 2021)
In an economy of „knowledge“ and information a competitive advantage can be created by the strategic management of intellectual capital. Relational capital in comparison to the other two elements of intellectual capital – human capital and structural capital, is formed and exists externally of the trading enterprise. The aim of the current article is to study the theoretical fundamentals of relational capital and its application in trade at a retail level. Thus a descriptive analysis has been carried out based on the results of a questionnaire conducted among managers of varying departments in retail chain stores, all enterprises registered as members of the Association for Modern Trade. The following work has endeavored to estimate the importance and value creating potential of relational resources as part of intellectual resources in the retail enterprise.
Keywords: Relational capital; Intellectual resources; Retail trade; Retail chains